2018
DOI: 10.1038/s41598-018-31756-0
|View full text |Cite|
|
Sign up to set email alerts
|

Particular CSF sphingolipid patterns identify iNPH and AD patients

Abstract: Idiopathic normal pressure hydrocephalus (iNPH) is characterized by reversible neurological symptoms due to an impairment in cerebrospinal fluid (CSF) clearance. In these patients, cognitive functions are severely impaired, with a scenario similar to Alzheimer’s disease (AD), making the differential diagnosis difficult and highlighting the need of new markers. We analyzed the composition of sphingolipids (SLs) in serum, by combining a single phase extraction with a high-performance thin-layer chromatography (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 59 publications
5
21
0
Order By: Relevance
“…The higher levels of ceramide species in plasma of AD patients is in accordance with a previous study that observed higher content of total ceramides in CSF of AD patients compared with the control group [52]. Likewise, a recent work that evaluated serum SL by high-performance thin layer chromatography (HPTLC)-densitometry observed higher long and short chain ceramides in AD compared to controls [53]. The consistency of results observed in plasma, serum and CSF of AD patients supports the idea of a general biofluid increase in ceramide levels at least for this disease.…”
Section: Sphingolipids In Neurodegenerative Diseases: Case-controlsupporting
confidence: 89%
See 2 more Smart Citations
“…The higher levels of ceramide species in plasma of AD patients is in accordance with a previous study that observed higher content of total ceramides in CSF of AD patients compared with the control group [52]. Likewise, a recent work that evaluated serum SL by high-performance thin layer chromatography (HPTLC)-densitometry observed higher long and short chain ceramides in AD compared to controls [53]. The consistency of results observed in plasma, serum and CSF of AD patients supports the idea of a general biofluid increase in ceramide levels at least for this disease.…”
Section: Sphingolipids In Neurodegenerative Diseases: Case-controlsupporting
confidence: 89%
“…Moreover, depending on the technique used to separate the molecules it is possible to identify the sphingoid base of each SM species, and therefore it is difficult to compare results from different studies at species level [46]. Table 3 shows the results obtained in two studies with AD patients [47,53], and single studies of PD [54], MS [55], and amyotrophic lateral sclerosis (ALS) [56]. SM species were found decreased in AD, PD and MS compared to controls (Table 3).…”
Section: Sphingolipids In Neurodegenerative Diseases: Case-controlmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the important functions of S1P is in modulating vascular biology; for example, it has been demonstrated that S1P is involved in endothelial barrier integrity, and vascular smooth muscle function [ 51 , 65 ]. Peripheral and CSF S1P has also been found to be altered in stenosis and stroke, a key event prior to onset of VCI [ 66 ] as well as in AD [ 67 ]. It is likely that peripheral S1P may also be affecting the CNS in indirect ways.…”
Section: Discussionmentioning
confidence: 99%
“…Sera samples were extracted according to the procedure of Alshehry et al . 51 , with minor modifications, as already described in 52 .…”
Section: Methodsmentioning
confidence: 99%